Search and Reallocation in the COVID-19 Pandemic: Evidence from the UK - Carlos Carrillo-Tudela; Camila Comunello; Alex Clymo; Annette Jäckle; Ludo Visschers; David Zentler-Munro (Institute of Labor Economics (IZA), 2021)
The impact of the Covid-19 pandemic on the UK labour market has been extremely heterogeneous, with strong variation both by occupation and industrial sector. The extent to which workers adjust their job search behaviour in response to this reallocation of employment has an important bearing on the future course of the labour market. At an aggregate level we see evidence consistent with search responding to changes to the state of the economy. In particular, changes to job search by employees are closely linked to changes in vacancies, and we also see ows from unemployment to inactivity peak at the same time as vacancies bottom-out. A key novelty in this paper is that we can additionally see whether the link between job search and changing employment patterns holds at a micro level, using the COVID supplement of the UK Household Longitudinal Survey, which shows the industries and occupations targeted by job searchers. The vast majority of job searchers target growing occupations and industries, which suggests job searchers are responding to conditions at a micro as well as macro level. This is also suggested by the fact that job searchers who were in occupations that expanded in the pandemic seek to switch occupations less frequently than those in shrinking occupations.
Keywords: E24; J23; J63; 330; job search; sectoral mobility; COVID-19